Can any one tell me why the answer to this problem: - (5x + 7) is
= -5x - 7
and not
= -5x + (-7)
Greatly appreciated if you can tell me. Thanks in advance.
They both mean the same thing, and to the expression originally given.Can any one tell me why the answer to this problem: - (5x + 7) is
= -5x - 7
and not
= -5x + (-7)
Greatly appreciated if you can tell me. Thanks in advance.
They're mathematically equivalent, but "simplified" form (the one without the parentheses) is considered more "proper". I would accept either form, but some instructors (and most computer assessments) won't accept the latter. Use with caution.Can any one tell me why the answer to this problem: - (5x + 7) is
= -5x - 7
and not
= -5x + (-7)